An Epistemic Look at Parental Conceptual Knowledge and Oral Health Outcomes in Children - Untray T. Brown DDS, MPH; Silvia Spivakovsky DDS; Malvin Janal PhD (SAGE Publishing, 2024)
Objective. This study explores the impact of parental oral health knowledge on children's oral health, investigating if limited knowledge contributes to poor outcomes. The CAMBRA caries risk assessment and the World Health Organization dmft/DMFT index measure oral health. Methods. Over 23 months, the Knowledge Related to Oral Health Literacy (KROHL) questionnaire assesses parental knowledge in 4 domains and 5 oral health conditions. Pearson Correlation Coefficient analyzes the association between KROHL scores and CAMBRA outcomes. Results. Positive correlation emerges between parental oral health knowledge levels and children's dental caries risk, indicating the KROHL questionnaire's utility in identifying knowledge gaps. No standardized method for measuring oral health knowledge exists, although various tools claim to address aspects of the issue. This study pioneers the correlation between oral health knowledge and CAMBRA outcomes. Conclusion. The KROHL questionnaire proves a practical, disease-specific tool for research, emphasizing parental oral health knowledge's pivotal role in children's oral health. It serves as a valuable means to identify knowledge gaps and potential areas for intervention and education in oral health.